Enabling Mode Changes in a Distributed Automotive System - Mitzlaff, Martin; Kapitza, Rüdiger; Schröder-Preikschat, Wolfgang (Proceedings of the 1st Workshop on Critical Automotive applications: Robustness & Safety, 2010)
Due to the high pressure for innovation, recent cars offer a constantly increasing number of sophisticated functions for advanced driver assistance and an improved active safety. As a result, software complexity in cars rises. Up to now, configurations of current automotive embedded systems are fixed and remain static over the vehicle lifetime. However, this is problematic as all offered functions have to be taken into account for the schedule of currently upcoming time-triggered bus systems and also the OS schedules on the electronic control units (ECUs). In principle, this is not necessary, as subsets of these functions have disjoint phases of use. This paper presents dynamic reconfiguration in cars based on mode changes, allowing to switch between a set of statically defined bus and ECUs schedules during runtime. This decreases the resource usage and the complexity of a specific set of bus and ECU schedules, as only active functions have to be considered. We outline how such a mode change can safely be enabled using a membership service for a time-triggered bus system and outline our experience in the context of a practical use case scenario: dedicated modes for normal operation and for servicing a car. © 2010 ACM.
UnivIS-Import:2015-04-16:Pub.2010.tech.IMMD.IMMD4.enabli
Keywords: FlexRay; membership; mode change; software-update; automotive; scheduling